Attenuation of noisy environment-induced neuroinflammation and dysfunction of learning and memory by minocycline during perioperative period in mice - Lin, Fei (Brain Res Bull, 2020)
Noisy environment often occurs in hospitals. We set out to determine whether noisy environment induces neuroinflammation and impairment of learning and memory and whether the effects of noise contribute to the development of neuroinflammation and impairment of learning and memory during the perioperative period. Seven-week old CD-1 male mice were exposed to noisy environment in the presence or absence of surgery (right carotid artery exposure). Noisy environment was 75 db, 6 h/day, for 3 days or 5 days. Minocycline (40 mg/kg), an antibiotic with anti-inflammatory property, was administered intraperitoneally 1 h before surgery or each episode of noise. The learning and memory of mice were assessed by Barnes maze and fear conditioning tests. Brain was harvested for the determination of interleukin (IL)-1β and IL-6 and for immunohistochemical staining. We found that noise induced learning and memory impairment. Noise also increased IL-1β, IL-6 and ionized calcium binding adapter molecule 1 (Iba-1) in the hippocampus. The combination of noisy environment and surgery induced dysfunction of additional domains of learning and memory and a higher expression of Iba-1 in the hippocampus. The effects of noisy environment or the combination of noisy environment and surgery were attenuated by minocycline. These findings suggest that noisy environment induces neuroinflammation and impairment of learning and memory. These effects may contribute to the development of neuroinflammation and dysfunction of learning and memory during the perioperative period. Neuroinflammation may be an underlying pathophysiological process for cognitive dysfunction induced by noise or the combination of noise and surgery. Minocycline may be effective in attenuating these noise-induced effects.